1985
DOI: 10.1002/jcu.1870130304
|View full text |Cite
|
Sign up to set email alerts
|

Compilation of reported biological effects data and ultrasound exposure levels

Abstract: A compilation of reports of biological effects and related ultrasound exposure levels can be useful in the identification of trends in effects data that may be developing in the literature. The exposures in the experiments reviewed were at frequencies used in medicine. For short (10 minutes or less) continuous wave exposure, with the exception of behavioral effects where variable results have been observed, this tabulation did not identify any in vivo or in vitro effects at spatial peak, temporal average (SPTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 98 publications
(26 reference statements)
0
6
0
3
Order By: Relevance
“…113 The National Center for Devices and Radiologic Health compiled the reported biologic effects of ultrasound before 1985, but interpretation and extrapolation of these results to humans is difficult because experimental models and methods varied substantially between studies. 153 Lack of standardized ultrasound exposure protocols or the use of baseline anesthesia are …”
Section: Limitations Of Studies Examining Biologic Effects Of Ultrasoundmentioning
confidence: 99%
“…113 The National Center for Devices and Radiologic Health compiled the reported biologic effects of ultrasound before 1985, but interpretation and extrapolation of these results to humans is difficult because experimental models and methods varied substantially between studies. 153 Lack of standardized ultrasound exposure protocols or the use of baseline anesthesia are …”
Section: Limitations Of Studies Examining Biologic Effects Of Ultrasoundmentioning
confidence: 99%
“…Após teste de emissão, determinou-se a calibração de acordo com os parâ-metros clínicos utilizados para tratamento da lipodistrofia. 11,13 A potência foi estabelecida em 1W/cm 2 , com 3MHz de freqüência, durante três minutos no modo pulsado com regime de pulso 2ms on: 8ms off. 20 Os animais foram posicionados em decúbito dorsal, tendo a pata direita sido apoiada sobre lâmina de borracha sintética para minimizar a reflexão do ultrasom.…”
Section: Methodsunclassified
“…6 O sistema circulatório tem a peculiaridade de interagir com o US, pois apresenta partículas em movimento e vasomotricidade baseada num complexo controle neuro-humoral. Respostas como alterações da coagulação, 7,8 fibrinólise, 9,10 vasomotricidade, 11 estímulo angiogênico e outras têm sido descritas em situações específicas e controladas empregando a terapia ultra-sônica (TUS); 12 entretanto, encontram-se poucos estudos referentes aos mecanismos biológi-cos do ultra-som no sistema circulatório.…”
Section: Introductionunclassified
“…Some studies have reported increased malformation rates (Stolzenberg et al, 1980a;Saravazayan et al, 1982;Takabayashi et al, 1985), while others have found no such effects (Kimmel et al, 1983(Kimmel et al, , 1989Gates, 1984, 1985;Child et al, 1984Child et al, , 1989Vorhees et al, 1991;Jensh et al, 1994). Furthermore, there are conflicting reports concerning the effects of ultrasound exposure on body weight and behavioral changes (Stewart et al, 1985;Hendrickx, 1989a, 1989b;Norton et al, 1991;Hande and Uma Devi, 1992, 1993Newnham et al, 1993;Vorhees et al, 1994;Uma Devi et al, 1995;Fisher et al, 1996;Suresh et al, 1996). Several human epidemiological studies strongly suggest the biosafety of prenatal diagnostic ultrasound exposure (NCRP, 1983;Stark et al, 1984;Meire, 1987;Ziskin and Petitti, 1988;Maulik, 1989;Salvesen et al, 1992Salvesen et al, , 1993Barnett et al, 1994;Suresh et al, 2002).…”
Section: Introductionmentioning
confidence: 99%